Application of molecularly imprinted polymers as artificial receptors for imaging. (1st January 2020) - Vaneckova, Tereza; Bezdekova, Jaroslava; Han, Gang; Adam, Vojtech; Vaculovicova, Marketa
Abstract: Medical diagnostics aims at specific localization of molecular targets as well as detection of abnormalities associated with numerous diseases. Molecularly imprinted polymers (MIPs) represent an approach of creating a synthetic material exhibiting selective recognition properties toward the desired template. The fabricated target-specific MIPs are usually well reproducible, economically efficient, and stable under critical conditions as compared to routinely used biorecognition elements such as fluorescent proteins, antibodies, enzymes, or aptamers and can even be created to those targets for which no antibodies are available. In this review, we summarize the methods of polymer fabrication. Further, we provide key for selection of the core material with imaging function depending on the imaging modality used. Finally, MIP-based imaging applications are highlighted and presented in a comprehensive form from different aspects. Statement of significance: In this review, we summarize the methods of polymer fabrication. Key applications of Molecularly imprinted polymers (MIPs) in imaging are highlighted and discussed with regard to the selection of the core material for imaging as well as commonly used imaging targets. MIPs represent an approach of creating a synthetic material exhibiting selective recognition properties toward the desired template. The fabricated target-specific MIPs are usually well reproducible, economically efficient, and stable under critical conditions as compared to routinely used biorecognition elements, e.g., antibodies, fluorescent proteins, enzymes, or aptamers, and can even be created to those targets for which no antibodies are available. Graphical abstract: Image, graphical abstract Synthetic materials with selective recognition properties toward templates are an alternative to traditionally used recognition biomolecules (e.g., antibodies). Key applications of molecularly imprinted polymers in imaging are highlighted and discussed with regard to the selection of the core material for imaging as well as commonly used imaging targets.